2020
DOI: 10.3390/s20030912
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Real-Time Tillage Depth Measurement System for Agricultural Tractors: Application to the Effect Analysis of Tillage Depth on Draft Force during Plow Tillage

Abstract: The objectives of this study were to develop a real-time tillage depth measurement system for agricultural tractor performance analysis and then to validate these configured systems through soil non-penetration tests and field experiment during plow tillage. The real-time tillage depth measurement system was developed by using a sensor fusion method, consisting of a linear potentiometer, inclinometer, and optical distance sensor to measure the vertical penetration depth of the attached implement. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 30 publications
1
25
0
Order By: Relevance
“…Moreover in increasing depth that increases the necessary with drawal requirements to overcome these forces. These results are consistented with the results which were obtained (Al-suhaibani and Gali, 2010; Kim et al, 2020). Also, it was found that the severed share significant outperformed the conventional shares and the spearhead in obtaining the lowest draft force at a rate of (6.99) kN compared to the remnant of the treatments,That was due to the lack of confrontation of the surface of the severed share through penetration with the lowest resistance and therefore the lowest draft force, but the increase in the draft force of the spearhead share, is due to an increase in its confrontation with the soil further, as a result of the increase in the area of the share facing the soil when penetration with the deep of the share and thus the increase in the draft force, and these results are consistent with what was reached (Alrijabo and Kashmola, 2013) where they confirmed that the draft force increases with an increase in the width of the share.…”
Section: ( )supporting
confidence: 93%
See 1 more Smart Citation
“…Moreover in increasing depth that increases the necessary with drawal requirements to overcome these forces. These results are consistented with the results which were obtained (Al-suhaibani and Gali, 2010; Kim et al, 2020). Also, it was found that the severed share significant outperformed the conventional shares and the spearhead in obtaining the lowest draft force at a rate of (6.99) kN compared to the remnant of the treatments,That was due to the lack of confrontation of the surface of the severed share through penetration with the lowest resistance and therefore the lowest draft force, but the increase in the draft force of the spearhead share, is due to an increase in its confrontation with the soil further, as a result of the increase in the area of the share facing the soil when penetration with the deep of the share and thus the increase in the draft force, and these results are consistent with what was reached (Alrijabo and Kashmola, 2013) where they confirmed that the draft force increases with an increase in the width of the share.…”
Section: ( )supporting
confidence: 93%
“…Manuwa and Ademosun (2007) and Jebur and Alsayyah (2017) found in their study of the influence of soil moisture content on the draft force, that the draft force increases as the soil moisture content increases, especially in clay soils. Increasing the depth of tillage of the chisel plow can lead to an increase in the draft force clearly (Al-suhaibani and Gali, 2010;Kim et al, 2020) where they observed when the speed was fixity, the draft force increased by a clear increase when increasing the depth of tillage from (11 to 19) cm. Al-Talabani et al (2015) explained in a field study that the roughness of tillage appearance is directly proportional to the increase in the depth of tillage because the sub-surface soil has a higher density and hardness than surface soil.…”
Section: ‫الــرافـديــن‬ ‫زراعـــة‬ ‫مـجـلـــة‬mentioning
confidence: 98%
“…In addition, in research related to agricultural machinery, it can be said that the draft force between the attachment plowing implement and the test soil directly affects the tractor load and power requirements according to the travel speed and slip ratio. In this field experiment, a commonly used six-component load cells system was used to measure the draft force [39,40]. The six-component load cells system consisted of six tensile compression-type universal type load cells (UU-T2, DACELL, Cheongju, Korea) to measure the 3-axis forces (horizontal, vertical, and lateral) that occurred during tillage operation.…”
Section: Load Measurement Systemmentioning
confidence: 99%
“…In order to analyze the effect of tillage depth, which is one of the most influential factors on mechanical load of agricultural machinery such as draft force, wheel axle load, engine load, and slip ratio, several studies on the development of real-time tillage depth measurement systems have been conducted [40,42]. In this field experiment, shortcomings (universality, durability) of the tillage depth measurement system developed in previous studies were improved and used for field experiment.…”
Section: Tillage Depth Measurement Systemmentioning
confidence: 99%
“…Because transplanter perform the task of penetrate the transplant hopper into the soil, the physical condition of the soil is one of the factors affecting the workload. Thus, the physical environment of the soil as a reference of the measured transplanter PTO load was obtained as shown in Figure 3b [19] . The soil moisture and electric conductivity were measured using a soil sensor (WT100B, RF sensor, Seoul, Korea).…”
Section: Experiments Methodsmentioning
confidence: 99%